The Investigation into Determinants of Regional Exports Base: Panel Analysis for Spanish and Polish Regions - Tomasz Brodzicki; Laura Márquez-Ramos; Stanisław Umiński (Entrepreneurial Business and Economics Review, 2018)
Objective: We use the small open economy concept to identify the determinants of region’s exports at a NUTS-2 level for Poland and Spain over the period 2005-2015.